Contact language formation in evolutionary terms - Ansaldo, Umberto (John Benjamins Publishing Company, 2009)
The aim of this paper is to present a view of contact language formation in which language creation in multilingual ecologies follows the same principles as language maintenance in monolingual ecologies, i.e. selection and replication of features available to speakers in a given environment. In order to do so, I introduce the foundations underlying an evolutionary framework to contact language formation and the views they offer for our understanding of language contact and change. The view of grammar as an evolving system, I believe, can be best appreciated in a functional-typological theory of language. For this reason, I first introduce the basic functionalist, usage-based linguistic theories required for an evolutionary framework. I then synthesize a view on language contact and change in evolutionary terms based on Croft (2000, 2006a) and Mufwene (2001). Finally, I apply the views presented here to a case of contact language formation, namely the evolution of case markers in a variety of Sri Lanka Malay. These are particularly interesting as, from a classic or orthodox view, they might be seen as ‘complex’, ‘marked’ or at least ‘unexpected’ instances of contact-induced change. The evolutionary framework however can explain these as natural acts of linguistic replication in multilingual settings, thus avoiding exceptionalist explanations. Instead, an evolutionary framework offers an integration of socio-historical and functional-typological observation, something that our current approaches to language change still largely lack (Croft 2006b). Among the advantages of the framework applied here, as discussed in the concluding section, is the suggestion that overall structural complexity, however defined, does not change as a result of contact language formation: a new grammar is simply the result of a recombination of grammatical features of the input languages.